An ethnographic study of social bonds In collective confinement - Ulutaş, Mete. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
This thesis explores the everyday life of political prisoners and the effects of incarceration after their release. In order to achieve this aim, the study employs the ethnographic data collected in the Silivri Prison and through participant observation and in-depth semi-structured interviews conducted with the prison inmates after their release. This study explores the prison and post-prison life of political prisoners collectively incarcerated in a ward. In particular, the study analyzes the imprisonment process by focusing on two significant events: the arrest and the release. In doing so, my analysis aims to show how political prisoners form social bonds among themselves and the effects of incarceration on their subjectivity after their release. In order to explore the subjectivation processes of political prisoners, my study analyzes the social-material setting of the prison space, the organization of everyday life in prison, and its contestation between the prison administration and the political prisoners. By elaborating on collective self-organization practices, identification, and subjectivation processes of political prisoners, the thesis examines how they make sense of their imprisonment. The study explores the reintroduction of the family as an institution where care relations are primarily designated and how political prisoners experience the public space in the post-prison life. This thesis proposes to take political prisoners as active agents of transformation within the prison space and beyond the narratives of total destitution and suffering. The main argument of the study is that the relations of care among the political prisoners transform the political ward into an intimate space.
Keywords: Political prisoners.